Assessment of the Patients\' Satisfaction about the Education Received from Their Physicians in Babol City - Ali ShabestaniMonfared; Seyed Jalil Seyedi-Andi; Seyed Abdolmotalleb Hasani-Hasankola; Javanian Mostafa; Iman Jahanian; Mostafa Mostafazadeh-bora; Hemmat Gholinia; Monireh Parvaneh (Babol University of Medical Sciences, 2015)
BACKGROUND AND OBJECTIVE: Quality of health care services depends on not only the competence of physicians, but also correct education to patients. This study aimed to investigate the patients;#39 satisfaction about education by their physicians in Babol city. METHODS: This was a descriptive-analytic and cross-sectional study which was performed on 300 patients referred to hospital clinics in Babol city in 2013. Our sampling method was as easy and available. Data collection tool was a researcher-constructed questionnaire that included two parts: 1-demographic variables 2-technical questions about the patients;#39 education. Data were analyzed by SPSS software, version 20 with the paired- T-test and ANOVA. FINDINGS: There is a significant correlation between etiology, symptoms and signs, complications and diagnosis with the physicians' education (p;le 0.05), most of the study subjects stated the average satisfaction about the physicians;#39 education. CONCLUSION: According to the results of this study in which the patients stated the average satisfaction about the physicians;#39 education in the most items and also considering that the patients;#39 education is an important element for development of community health promotion, performing planned in-service workshops for physicians about communication skills and patients;#39 education is suggested.